Analysis of Financial Ratio in Assessing Financial Performance - Edison Hamid (Peneliti.net, 2021)
This study aims to determine the financial performance of the company PT. Indofood Sukses Makmur, Tbk. With the financial ratio analysis method consisting of liquidity ratios including, current ratio, quick ratio and cash ratio, solvency ratio includes debt ratio and debt to equity, activity ratio includes receivable turn over, inventory turn over, fixed assets turn over and total asset turn over, and profitability ratios include gross profit margin ratio, net profit margin ratio, return of equity and return of assets. The data used in this research is secondary data. Data collection techniques using library techniques and documentation techniques. The data analysis technique used was quantitative descriptive analysis technique. Based on the results of data analysis and discussions that have been carried out at PT. Indofood Sukses Makmur, Tbk. 2015-2019, it can be concluded that the financial performance of PT. Indofood Sukses Makmur, Tbk. when viewed from the liquidity ratio of PT. Indofood Sukses Makmur, Tbk. which has been measured using CR and QR is non-liquid, while the Cash Ratio is liquid. The solvency ratio that has been measured using DAR and DER is not good. The activity ratio that has been measured using RTO, ITO, FATO, and TATO is not good. The profitability ratios that have been measured using GPM, NPM, ROE, and ROA are very good and efficient.